1975
DOI: 10.2134/jeq1975.00472425000400010005x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Timber Harvesting and Related Management Practices on Water Quality in Forested Watersheds

Abstract: Undisturbed forested watersheds are generally recognized as a primary source of high‐quality water. The physical and chemical nature of these waters fluctuate constantly in response to natural stresses but are most influenced by man's activities. Three major forest land management activities—timber harvesting, fertilization, and herbiciding—which may have an adverse affect on water quality are reviewed. In general, research results indicate that nutrient losses, particularly nitrogen, following forest clearcut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
9

Year Published

1979
1979
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 0 publications
1
11
0
9
Order By: Relevance
“…Initial increases in streamwater chemical concentrations following the treatments are probably due to alterations in forest nutrient cycling pathways [e.g., Fredriksen et al, 1975;Sopper, 1975;Vitousek, 1977;Stone et al, 1978]. Vitousek and Reiners [1975] proposed that nutrient loss from watersheds was controlled to a large extent by net biomass increment or net accumulation of nutrients in living and dead biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Initial increases in streamwater chemical concentrations following the treatments are probably due to alterations in forest nutrient cycling pathways [e.g., Fredriksen et al, 1975;Sopper, 1975;Vitousek, 1977;Stone et al, 1978]. Vitousek and Reiners [1975] proposed that nutrient loss from watersheds was controlled to a large extent by net biomass increment or net accumulation of nutrients in living and dead biomass.…”
Section: Discussionmentioning
confidence: 99%
“…The watersheds lie in the dry subzone of the Coastal West-1970] may occur, while dissolved oxygen levels may decrease ern Hemlock biogeoclimatic zone of British Columbia [Kra- [Hall and Lantz, 1969]. These results have been reinforced by jina, 1969] and are covered mainly with Tsuga heterophylla more recent studies as summarized by Bell et al [1974] and (western hemlock), Thuja plicata (western red cedar), and Sopper [ 1975].…”
Section: Introductionmentioning
confidence: 97%
“…The unanimous conclusion of these studies is that forest cutting does not threaten water or site quality and that stream water nutrient concentrations are quickly reduced with revegetation of the site (Brown, et at!, 1973;Cole, et aL, 1973;DeByle and Packer, 1972;Fredriksen, et aL, 1975;Stark, 1979;Aubertin and Patric, 1974;Corbett, e t a l , 1978). Sopper (1975) reviewed research results on the effect of forestry practices on water quality and concluded that "results indicate that nutrient losses following forest clearcutting are small to negligible" and the "amounts of nutrients discharged following clearcutting are generally small in terms of the total nutrient capital and should not reduce site productivity.'' Patric (1978), in a summary of the effects of timber harvesting on soil and water in the eastern hardwood forest states, "There is overwhelming evidence that neither productivity of forest soil nor the quality of forest water are substantially lessened during or after responsibility managed harvests of wood products.…”
Section: Introductionmentioning
confidence: 99%